In vivo monitoring of fetoplacental Vegfr2 gene activity in a murine pregnancy model using a Vegfr2-luc reporter gene and bioluminescent imaging - Rude Brian J; Bowers Susan D; Dunaway Chad W; Greene Jonathan M; Feugang Jean M; Ryan Peter L (Reproductive Biology and Endocrinology, 2011)
Abstract Background Vascular endothelial growth factor receptor-2 (VEGFR2) plays a pivotal role in angiogenesis by eliciting vascular endothelial cell growth when bound to VEGF, a powerful pro-angiogenic ligand. While Vegf and Vegfr2 are expressed throughout gestation, the latter third of gestation in mice is characterized by a marked increase in fetoplacental angiogenesis. Thus, the objective of this study was to determine the feasibility of monitoring fetoplacental Vegfr2 gene activity non-invasively using a Vegfr2-luc reporter transgenic mouse and bioluminescent imaging. Methods Imaging parameters were optimized using two wild-type (WT) females, bearing Vegfr2-luc fetuses. Then, seven WT females, bred to Vegfr2-luc males, were imaged from gestational day (GD) 12 to 18 to determine the usefulness of the Vegfr2-luc mouse as a model for studying fetoplacental Vegfr2 activity during pregnancy. Semi-quantitative RT-PCR of Vegfr2 was also performed on whole fetoplacental units during this time. Additionally, resultant neonates were imaged at postnatal day (PND) 7, 14 and 21 to monitor Vegfr2 activity during post-natal development. Results Fetoplacental Vegfr2 gene activity was detected as light emissions beginning on GD 12 of gestation and increased throughout the imaging period (P < 0.05), and this paralleled the Vegfr2 mRNA data obtained from RT-PCR analysis. A decline in fetoplacental light emissions was associated with a poor pregnancy outcome in one pregnancy, indicating that this approach has potential use for studies monitoring pregnancy well being. Additionally, neonatal Vegfr2 activity was detected at PND 7, 14 and 21 but declined with time (P < 0.0001). Conclusions In utero fetoplacental Vegfr2 gene activity was monitored longitudinally in a quantitative manner using a luciferase reporter gene and bioluminescent imaging during the latter third of gestation. This study demonstrates the feasibility of using the Vegfr2-luc mouse to monitor late gestation fetoplacental angiogenic activity under normal and experimental conditions. Additionally, neonatal Vegfr2 gene activity was monitored for three weeks postpartum, allowing continuous monitoring of Vegfr2 activity during the latter third of gestation and postnatal development within the same animals.